Juan Cunha - Etchegorry, F (Cirugía del Uruguay, 2020)
The disappearance of Prof. Juan Cunha produces a vacuum in the National Radiology difficult to fill, and therefore the surgeons also lose a collaborator whose absence will be miss for a long time.